2009
DOI: 10.1097/meg.0b013e32832ca091
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of oesophageal and stomach cancer subtypes in Europe

Abstract: Our results are partly in line with earlier findings on adenocarcinomas of the oesophagus and gastric cardia. There was, however, substantial heterogeneity in trends of subtypes of these cancers within Europe. There may be different risk factors for these cancers, and the prevalence of these risk factors may differ among countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
138
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 28 publications
5
138
1
7
Order By: Relevance
“…The incidence of upper-third gastric cancer including cancer of the gastroesophageal junction has been increasing steadily in Western countries, even though the incidence of gastric cancer is on the decline [1][2][3]. A similar trend has been observed in Japan and in Eastern countries in recent decades [4,5].…”
Section: Introductionmentioning
confidence: 57%
“…The incidence of upper-third gastric cancer including cancer of the gastroesophageal junction has been increasing steadily in Western countries, even though the incidence of gastric cancer is on the decline [1][2][3]. A similar trend has been observed in Japan and in Eastern countries in recent decades [4,5].…”
Section: Introductionmentioning
confidence: 57%
“…In addition to environmental factors, genetic factors also play an important role in GC etiology, and previous reports suggest that combinations of genetic and/or epigenetic changes in oncogenic and tumor suppressor pathways may drive GC [10][11][12]. Based on cancer epidemiology, pathological characteristics, and tumor location, GCs can be categorized into three distinct malignancies arising in the same organ: (1) proximal nondiffuse cancers of the cardia and gastroesophageal junction, which are rapidly increasing in incidence in the Western Hemisphere and are related to lifestyle factors, obesity, and chronic gastric acid reflux; (2) diffuse-type GC derived from poorly differentiated or signet-ring cell adenocarcinoma; and (3) distal nondiffuse intestinal-type GC, linked to precursor lesions arising from atrophic gastritis and chronic inflammation related to Helicobacter pylori [11,[13][14][15]. Genetic background according to ethnicity may be related to differences in the histological and anatomical subtypes of GC; therefore, analysis taking into account GC subtypes is necessary to clarify molecular mechanisms of GC carcinogenesis and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported a continuing rise in the incidence of adenocarcinoma of the gastroesophageal junction (GEJ) despite a decline in the overall incidence of gastric carcinoma in Western countries [1,2]. Adenocarcinoma of the GEJ is defined as carcinoma centered within 5 cm of the anatomic GEJ, which is further classified into three distinct entities (types I, II, and III) according to the anatomic location of the tumor center [3,4].…”
Section: Introductionmentioning
confidence: 99%